2002
DOI: 10.1038/sj.eye.6700031
|View full text |Cite
|
Sign up to set email alerts
|

Retinopathy of prematurity: are we screening too many babies?

Abstract: Purpose With advancement in neonatal care units, early detection of retinopathy of prematurity (ROP) in premature and verylow-birth-weight infants is important. Numerous studies have reported an increased risk of ROP in prematurely born infants, but only few have been long-term and strictly population-based. The aim of the present study was to find out whether birthweight Ͻ1251 grams and gestational age Ͻ30 weeks could provide a safe and efficient means of detecting treatable ROP. We have retrospectively tried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
38
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 20 publications
7
38
0
2
Order By: Relevance
“…While we adopt the Royal College Recommendations of screening infants less than 1500 g, we are in agreement with studies [13][14][15] that recommend lowering the BW criterion for screening infants for ROP to 1250 g. None of our patients over 1250 g developed tROP. This would have decreased the number of babies screened by 38% in our study.…”
Section: Eyesupporting
confidence: 82%
“…While we adopt the Royal College Recommendations of screening infants less than 1500 g, we are in agreement with studies [13][14][15] that recommend lowering the BW criterion for screening infants for ROP to 1250 g. None of our patients over 1250 g developed tROP. This would have decreased the number of babies screened by 38% in our study.…”
Section: Eyesupporting
confidence: 82%
“…Recently, both retrospective and prospective studies have reported the frequency and severity of ROP in a wide range varying from hospital to hospital and from population to population (28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). There are limited number of prospective, multicenter studies performed in different populations.…”
Section: Discussionmentioning
confidence: 99%
“…She did not require re-ventilation and had not suffered prolonged anoxic or hyperoxic states both of which are known to be associated with ROP. 10,11 Other perinatal factors were hyponatremia, hypoglycaemia, conjugated hyperbilirubinemia, compensated acute renal failure, bilateral intraventricular haemorrhage and staphylococcal sepsis. These features are not uncommon in preterm babies and have not found to be independent risk factors in the development of ROP.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 Though birth weight and GA are the two most important independent risk factors for this disease, not all factors contributing to the cause of ROP are yet known. The desire to decrease the number of unaffected babies to be screened should not prevent us from missing some of those cases that may provide valuable insight into the pathogenesis of this disease.…”
Section: Discussionmentioning
confidence: 99%